Surgery for metastatic spinal differentiated thyroid cancer: feasibility, outcome, and prognostic factors - Liu, Xiajun; Hu, Panpan; Zhai, Shuheng; Liu, Xiao; Wang, Ben; Zhou, Hua; Liu, Xiaoguang; Liu, Zhongjun; Wei, Feng (Frontiers in Surgery, 2023)
Study design: A retrospective cohort study. Objectives: This study aims to report the surgical outcome of metastatic spinal differentiated thyroid cancer (MSDTC) and analyze the factors affecting the prognosis. Methods: Thirty-five patients were recruited in our single institution who underwent spinal surgery and adjuvant therapies from 2009 to 2019. Two surgical procedures, total en-bloc spondylectomy and debulking surgery, were undertaken. Their clinical data, postoperative events, and survival data were collected and analyzed. Survival time and associated factors were further analyzed. Results: The cohort had a median survival time of 60 months. The mean visual analog scale scores and the Karnofsky performance score improved postoperatively (p<0.05). The patients’ Frankel grade was elevated for cases with preoperative neurological deficits (p<0.05). In 31 patients who underwent debulking surgery, 41.9% (n=13) had local recurrences, and radiotherapy reduced the risk of local relapse (p<0.05). Preoperative and postoperative Frankel grades and radioactive iodine (RAI) therapy were associated with the patients’ survival in the univariate analysis (p<0.05). Furthermore, a multivariate regression analysis showed the postoperative Frankel grade as an independent prognostic factor. Conclusion: Pain, quality of life, and neurological status of patients can be effectively improved after surgery. Radiotherapy can reduce the risk of local recurrences, whereas RAI therapy has a limited effect on local and extraspinal tumor control. Neurological status was independently associated with the patients’ survival.